Does It Matter Who Cares for You? The Effect of Substituting Informal with Formal Personal Care on the Care Recipients' Health - Bruce Hollingsworth; Asako Ohinata; Matteo Picchio; Ian Walker (Institute of Labor Economics (IZA), 2022)
We show that a Scottish policy reform, which introduced free formal personal home care for those aged 65 and above, reduced the probability and the hours of receiving informal personal care. Moreover, we find that the group of individuals that most benefited from the policy introduction, i.e. women aged 75 and above, experienced the largest fall in informal care. We go on to investigate whether such reductions in informal and increases in formal personal care impacted on the care recipients' health outcomes. Our results demonstrate that switching from informal to formal care does very little to the recipients' hospital usage and health outcomes.
Keywords: C21; D14; I18; J14; 330; long-term elderly care; ageing; financial support; difference-in-differences